2003
DOI: 10.1002/gcc.10231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate tumor‐suppressor genes in 6q27 by combined deletion mapping and electronic expression profiling in lymphoid neoplasms

Abstract: Deletions in the long arm of chromosome 6 (6q) are among the most frequent chromosome aberrations in lymphoid neoplasms. Recently, the region of minimal deletion (RMD1) in 6q27 was narrowed down to 5-9 Mb. In the present study, we aimed to define the distal border of the commonly lost region in 6q27 more precisely and to identify and investigate tumor-suppressor genes (TSGs) from this region. Twenty-nine cases, in which our previous fluorescence in situ hybridization (FISH) screening that used a set of 36 YAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…56 The regions of minimal common 6q deletion vary with disease type, suggesting that different tumor suppressor genes might be affected in each of these neoplasms. [57][58][59] In BL cell lines these deletions are consistently associated with loss of heterozygosity in the 6q25-27 region. 56 Genes possibly affected by 6q abnormalities include BACH2 (encoding for B-lineage specific transcription factor, a putative tumor suppressor gene), on 6q15, 60,61 and BLIMP1 (B-lymphocyte maturation promoting), on 6q21-q22.1.…”
Section: Discussionmentioning
confidence: 99%
“…56 The regions of minimal common 6q deletion vary with disease type, suggesting that different tumor suppressor genes might be affected in each of these neoplasms. [57][58][59] In BL cell lines these deletions are consistently associated with loss of heterozygosity in the 6q25-27 region. 56 Genes possibly affected by 6q abnormalities include BACH2 (encoding for B-lineage specific transcription factor, a putative tumor suppressor gene), on 6q15, 60,61 and BLIMP1 (B-lymphocyte maturation promoting), on 6q21-q22.1.…”
Section: Discussionmentioning
confidence: 99%
“…Both PDCD2 and BCL6 interact with N-CoR/ mSin3A corepressor complexes, which repress transcription by recruiting histone deacetylase (14,25), and PDCD2 has been shown to negatively regulate host cell factor 1, a multidomain protein required for cell cycle progression (25). Human PDCD2 is located on chromosome 6q27, a region where translocations have been reported in acute myelogenous leukemias and where deletions may occur in cutaneous T cell lymphomas, acute lymphoblastic leukemias (23), and non-Hodgkin lymphomas, including follicular B cell lymphoma (26), and it is believed to contain a putative tumor suppressor gene (27,28). Fan et al (29) found that PDCD2 was among several other proapoptosis genes that were expressed in decreased levels in a multidrug-resistant human colon carcinoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The results were concordant with the SNP array data in that all three abnormalities were confirmed and no additional regions of allelic imbalance were found (Figure1b and data not shown). Interestingly, loss of 6q material is a frequent aberration in nonHodgkin lymphoma and is also occasionally found in myelodysplastic syndromes (MDS) (Steinemann et al, 2003;Mitelman et al, 2006). Gain of 3q is associated with clonal evolution from Fanconi anemia to MDS (To¨nnies et al, 2003).…”
mentioning
confidence: 99%